2021
DOI: 10.1108/imds-01-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

How social enterprises gain cognitive legitimacy in the post-pandemic period? Social welfare logic and digital transformation

Abstract: PurposeThis paper aims to propose a social enterprise legitimation mechanism by combining the established logic and transformational logic to test the validity of the conceptual model.Design/methodology/approachThe authors construct the theoretical framework based on integrating organizational identity theory, attention-based view and collected 128 social enterprises data during the post-pandemic period in China. The authors applied multiple hierarchical regression analysis and mediation analysis to test the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…These study results are in line with the survey conducted by Borzaga and Tallarini (2021) that confirmed the ability of social enterprises to respond to the crisis with flexibility and see opportunities in emerging social needs. Social entrepreneurs learned from a negative event and started thinking of transformation (Borzaga, & Tallarini, 2021;Kishnani, 2022;Aisaiti et a., 2021;Bhardwaj & Srivastava, 2021). Furthermore, our study results conform with findings of Loukopoulos and Papadimitriou (2021) that the Greek social enterprises applied different approaches to respond to the challenges and enhance their social impact as an opportunity.…”
Section: Discussionsupporting
confidence: 89%
“…These study results are in line with the survey conducted by Borzaga and Tallarini (2021) that confirmed the ability of social enterprises to respond to the crisis with flexibility and see opportunities in emerging social needs. Social entrepreneurs learned from a negative event and started thinking of transformation (Borzaga, & Tallarini, 2021;Kishnani, 2022;Aisaiti et a., 2021;Bhardwaj & Srivastava, 2021). Furthermore, our study results conform with findings of Loukopoulos and Papadimitriou (2021) that the Greek social enterprises applied different approaches to respond to the challenges and enhance their social impact as an opportunity.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence suggests that social enterprises can strengthen their cognitive legitimacy-the perceived judgement of an organisation's acceptability-by reinforcing their identity and prioritising digital transformation. For example, Aisaiti et al (2021) analysed data from 128 social enterprises in China and found a positive correlation between social welfare logic and digital transformation. Furthermore, their study found that these factors can mediate the relationship between organisational identity and cognitive legitimacy.…”
Section: Prior Studies On Digital Transformation and Hypothesis Devel...mentioning
confidence: 99%
“…By enhancing limited organizational attention and smartly allocating internal resources, social enterprises can strengthen their trust and accountability towards governments or private investors who value efficiency. This ultimately increases legitimacy while simultaneously accelerating social impact through efficient digital solutions (Aisaiti et al., 2021).…”
Section: Findings and Analysismentioning
confidence: 99%